REPRESENTASI HERO DALAM FILM KUNG FU PANDA - Sugani Jiyantoro (LP3 UMY, 2015)
This research attempts to analyze the representotion of hero in Kung Fu Panda film. The theoretical framework used in this research is communication os process of meaning production, film as a medium of communication, representation, ond hero. The research method applied in this reseorch is semiotics analysis from Rolond Barthes, lt refers to two order of signification, the first ol signification is to find denotation sign, and second of signification is to find conotation sign. The result of this reseorch shows that hero in Kung Fu Pando Film is constructed through several form; firstly, physical, hero in this film hos corpulent and fat body. Secondly, sociol closs, hero is lrom the lower closs, Finally, personality, hero has confidence, modest, humorist, cleover, dominate, and lonely hero,